2014
DOI: 10.1007/s00170-014-6593-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cutting speed and tool wear on the surface integrity of the titanium alloy Ti-1023 during milling

Abstract: This study focuses on the machined surface integrity of the titanium alloy Ti-10V-2Fe-3Al (Ti-1023) during face milling. Surface roughness, machining defect, microhardness, and microstructure variations are investigated at different cutting speeds and tool average flank wear (VB) values. Experimental results show that surface roughness increases when cutting speed is increased from 40 to 100 m min −1 and decreases when cutting speed is increased from 100 to 300 m min −1 by using a new tool. Moreover, surface r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 34 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…The microhardness at the machined surface can significantly (e.g. 70-90%) increase when compared with that of the bulk material [54,77]. This aspect is of high relevance when considering the contact conditions between the different components of the implants as well as with the host organs (Fig.…”
Section: Titanium-based Alloysmentioning
confidence: 99%
“…The microhardness at the machined surface can significantly (e.g. 70-90%) increase when compared with that of the bulk material [54,77]. This aspect is of high relevance when considering the contact conditions between the different components of the implants as well as with the host organs (Fig.…”
Section: Titanium-based Alloysmentioning
confidence: 99%
“…Much of the research devoted to the study of surface roughness in face milling (Diniz and Filho 1999;Caldeirani Filho and Diniz 2002;De Souza et al 2003, 2005De Escalona and Maropoulos 2010;Prasad et al 2011;Houchuan et al 2015;Liu et al 2016;Shi et al 2016;Werda et al 2017) takes tool wear into account. Diniz and Filho (1999) studied the influence of the relative positions of tool and workpiece on tool life, tool wear, and surface finish in the face milling process, taking tool wear into account.…”
Section: Introductionmentioning
confidence: 99%
“…Prasad et al (2011) studied the impact of offsets due to vibration during face milling and the correlation of surface roughness with tool wear under different cutting conditions while monitoring the tool state. Houchuan et al (2015) investigated surface roughness, machining defects, microhardness, and microstructure variations at different cutting speeds and tool average flank wear values in the face milling of a titanium alloy, Ti-10V-2Fe-3Al (Ti-1023). Liu et al (2016) investigated the process of tool damage and its effect on machined surface roughness in high-speed face milling of 17-4PH stainless steel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behaviour was caused by different wear states of tool flank face. However, Yang et al [27] reported contradictory results, in which the machined surface roughness of TB6 presented an increasing trend with the increase of tool flank wear. Tool wear also had significant influence on residual stress and microhardness.…”
Section: Introductionmentioning
confidence: 99%